The Constitution and the national legal system - García Toma, Víctor (2015)
By which rules and principles does our sources oflaw system work? What is the relevance of our Constitution and of the Constitutional Court in thematter?In this article, the renowned constitutionalist falls in on these topics with a detailed work, but he also traces a path through our legal system, describing the norms it consists of according to their hierarchyin “the pyramid”.